2021
DOI: 10.3168/jds.2020-18884
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and textural characteristics and volatile compounds of semihard goat cheese as affected by starter cultures

Abstract: Today, cheese is valued because of its high nutritional value and unique characteristics. Improving the texture and flavor of cheese by selecting suitable starter cultures is an important way to promote the development of cheese industry. The effect of starter cultures on the physicochemical and textural properties and volatile compounds during the ripening of semihard goat cheese were investigated in this work. Different starter cultures-mesophilic (M) and thermophilic starters (T), Lactobacillus plantarum ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 49 publications
1
11
2
Order By: Relevance
“…garvieae were observed, but in general, these microorganisms did not affect these parameters on soft-ripened cheeses. These results contrast with those found by Jia et al [ 23 ] in semi-hard goat cheese, who reported that the addition of selected starter cultures could decrease the pH of matured cheese.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…garvieae were observed, but in general, these microorganisms did not affect these parameters on soft-ripened cheeses. These results contrast with those found by Jia et al [ 23 ] in semi-hard goat cheese, who reported that the addition of selected starter cultures could decrease the pH of matured cheese.…”
Section: Resultscontrasting
confidence: 99%
“…A total of 34 volatile compounds were identified in all the three analyzed batches of “Torta del Casar” cheese throughout the 90-day ripening including carboxylic acids, alcohols, aldehydes, ketones and esters ( Table 2 , Table 3 and Table 4 ). Most of the identified compounds have also been reported in other studies of “Torta del Casar” cheeses and other types of similar soft-bodied cheeses [ 22 , 23 , 30 ].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The pH values of the cheeses after production and during storage were above 5, which is the typical pH value for unpasteurized, semi-hard cow cheeses. Lowering the pH of milk through the production of lactic acid directly affects the stability of casein micelles and milk minerals [ 35 ]. The variation in pH value depends on the buffering capacity of the cheese and the amount of protein.…”
Section: Resultsmentioning
confidence: 99%
“…This is a consequence of the demineralization that occurs during the coagulation and removal of the whey. The acidity of cheeses changes during storage and, similar to the pH values, it may rise at first and then fall [ 35 ].…”
Section: Resultsmentioning
confidence: 99%